Effects of externally applied electrical stimulus on brain relationship during isometric contraction of hand muscle [electronic resource] - Suriani Hasan, 1979-; Fakulti Kejuruteraan Elektrik (2008)
Thesis ( Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi )) - Universiti Teknologi Malaysia, 2008